The interplay of philosophies and methods used in the design of assessments in the South African insurance industry. - Rogers, William (My University, 2010)
The insurance sector in South Africa is currently governed by the requirements of the South African Qualifications Act (Act No. 58 of 1995), which delegates it to the Insurance SETA (INSETA), an appointed Sectoral, Education and Training Authority (SETA), In the past, most insurance-related training and development centred on insurance process training, and although the workplace requirements have not changed, the requirements of the qualifications have. This has potentially led to tension in the industry, in that the INSETA is arguably designing standards and qualifications along behaviourist lines. This research report confirms whether or not this situation is the case. It also looks at the way the developers of the assessment tools for the unit standards and qualifications have potentially altered their methods of practice or alternatively, adopted a different philosophical stance to comply with INSETA requirements. Triangulated research was conducted using a defined set of respondents from a local perspective. The findings showed that no one respondent clearly displayed a particular philosophical standpoint and that, in every case, his or her assessment tool development methodology was in line with INSETA required practice.